Analysis of The Effect of Service Digitalization, Product Quality, and Service on SME Customer Satisfaction in Bengkulu City - Muhammad Bima Eka Putra (Penerbit Jurnal Indonesia, 2025)
This research, conducted by Arhau Mukmin and Dimas Aldi Pratama, aims to analyze the influence of service digitalization, product quality, and service quality on customer satisfaction among MSMEs (Micro, Small, and Medium Enterprises) in Bengkulu City. A quantitative approach was used, with data collected through questionnaires distributed to 100 respondents, and analyzed using multiple linear regression. The results indicate that all three independent variables have a positive and significant effect on customer satisfaction. Among them, service digitalization had the most dominant influence in enhancing transaction convenience and efficiency. It is recommended that MSME actors continue adopting digital technologies and consistently improve their product and service quality. The study is limited in scope, focusing only on three variables and a specific geographic area—Bengkulu City. Future research is suggested to explore additional variables such as pricing, customer loyalty, and marketing strategies to gain a more comprehensive understanding of customer satisfaction in the MSME sector.